PRIMARY ALDOSTERONISM UNVEILED BY PREGNANCY - Khor, K; Kamaruddin, NA; Sukor, N (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Primary aldosteronism (PA) with first presentation during pregnancy is rare. We hereby report 2 cases of PA which was unveiled by pregnancy. RESULTS Case 1: A 33-year-old female was diagnosed to have hypertension with hypokalaemia (lowest serum potassium of 2.3mmol/L) during early pregnancy. The pregnancy was complicated by intrauterine death at 29 weeks of gestation. Throughout pregnancy, her blood pressure (BP) and potassium levels were well-controlled with low-dose methyldopa` and potassium supplementation. Postpartum, she was normokalaemic without potassium supplementation and her BP was well-controlled with low-dose verapamil. She had a positive screening test for PA which was further confirmed with fludrocortisone suppression test (FST). Computed Tomography (CT) of the adrenal glands showed bulky appearance with no definite adenoma. Adrenal venous sampling (AVS) was suggestive of bilateral adrenal hyperplasia (BAH). Spironolactone was not started as she is planning for another pregnancy. To date, her BP was well-controlled with low-dose labetolol and she remained normokalaemic. Case 2: A 40-year-old female was diagnosed to have hypertension at 18 weeks of gestation with concomitant hypokalaemia (lowest serum potassium of 3.3mmol/L). Throughout pregnancy (while not on any medications) her BP ranged between 130/90 to 150/90 and serum potassium levels between 3.5 to 3.8 mmol/L. She underwent emergency caesarean section for pre-eclampsia at 36 weeks of gestation. Postpartum ambulatory blood pressure monitoring revealed SBP of 111-158 mmHg, DBP of 64-102 mmHg. Her screening test for PA was positive and was further confirmed with fludrocortisone suppression test. CT adrenals showed bulky appearance with no definite adenoma. AVS was suggestive of BAH. Upon commencement of spironolactone 12.5 mg daily, her BP was maintained at 110/80-128/90 mmHg and serum potassium was 4.0mmol/L. CONCLUSION PA is associated with high rate of pregnancy-related complications. The course of PA during pregnancy is highly variable owing to the sequential changes in the reninangiotensin-aldosterone system and plasma progesterone concentration.